A composiç\~ao da estrutura de financiamento do Pronaf para a agricultura familiar no centro-oeste no período de 2013 a 2023: Um longo caminho para o processo de comoditizaç\~ao? - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The objective of this investigation was to analyze how the financing structure of the National Program for Strengthening Family Farming of Family Farming in the Central-West Region is characterized in terms of its location and regionalization aspects in the period from 2013 to 2023. Thus, the Uncovered empirical evidence reinforces the argument that the distribution of Pronaf resources for agricultural activities in the Central-West region for the year 2023 concentrated just over 87% of the resources distributed by Pronaf in the agricultural activity of soybeans and corn. If cassava, pineapple, banana, tomato and rice are added, these seven selected crops concentrated 95.5% of the total resources distributed by Pronaf for agricultural activity, in a total of 40 crops, in this regional space. In other words, there are signs that the development style of the Central-West region, given its agrarian structure concentrated on medium and large agricultural properties, is further driving the specialization of family farmers for the production of agricultural commodities
Keywords: R11; 330; family farming; agricultural commodities; Pronaf